Literatur Review Artikel : MANFAAT PENGUJIAN AMILUM DAN PROTEIN PADA LARUTAN GLUKOSA, PATI (UJI MOLISCH) DENGAN MENGGUNAKAN BERBAGAI METODE - Fikayuniar, Lia; Putri, Nurhaliza; Candra, Ayu; Susanto, Nabila Tsabitah; Rahayu, Mega Septiani; Azalia, Riza Khaila; Azizah, Sella Siti Nur (Fakultas Farmasi Universitas Buana Perjuangan Karawang, 2024)
The testing of starch and protein in glucose and starch solutions was conducted using the Molisch test and other methods. Glucose, as a monosaccharide, serves as the main energy source, while starch, being a polysaccharide, must first be broken down into monosaccharides before it can be utilized. Carbohydrates, such as glucose and starch, provide energy and support food metabolism and characteristics such as taste, color, and texture. The methods applied in this review include literature studies on the chemical testing of starch and protein, focusing on the Molisch test for detecting carbohydrates in biological samples. Various approaches, including color-change-based methods and other analytical techniques, were used to measure starch and protein in glucose and starch solutions. The review findings highlight the importance of a thorough understanding of starch characteristics and its modification to enhance its utility in the food and pharmaceutical sectors. These findings support the use of pregelatinized starch and the exploration of alternative carbohydrates sources to improve food quality and variety. Qualitative tests, such as Benedict's, detect reducing sugars in foods, while temperature increases affect the moisture content and compaction of starch, especially in pregelatinized cassava starch. In conclusion, starch testing methods like iodine and Molisch tests are effective for analyzing starch and carbohydrates, while the ratio of starch to water and temperature play key roles in influencing the physical properties of starch.